2018
DOI: 10.1155/2018/7267164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1-Methylcyclopropene Treatment on Physicochemical Attributes of “Hai Jiang” Yardlong Bean during Cold Storage

Abstract: The yardlong bean belongs to nonclimacteric fruit. The objective of this study was to investigate the effects of 1-methylcyclopropene (1-MCP) treatment on physicochemical characteristics of yardlong beans during cold storage. Freshly harvested yardlong beans were treated with different concentrations of 1-MCP (0, 0.75, 1.0, 1.25, and 1.5 μL ·L−1) and stored at 8°C for 21 days. The results showed that, compared with the control, the decrease in firmness and good fruit rate and the degradation of chlorophyll and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The highest vitamin C content in fruit treated with 1.0 μl L –1 and 1.5 μl L –1 1-MCP compared to the control and 0.5 μl L –1 1-MCP treatments during storage suggests that higher concentration of 1-MCP may have a suppressive effect on peppers ( Win et al, 2006 ). The highest vitamin C content obtained under the 1.5 μl L –1 treatment during 12 days of storage was in agreement with the previous study by Jiang et al (2018) , who reported that a high concentration of 1-MCP maintained the vitamin C content of yardlong beans after 21 days of storage. According to Lee and Kader (2000) , vitamin C is an antioxidant that reacts with and neutralizes singlet oxygen and other free radicals.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The highest vitamin C content in fruit treated with 1.0 μl L –1 and 1.5 μl L –1 1-MCP compared to the control and 0.5 μl L –1 1-MCP treatments during storage suggests that higher concentration of 1-MCP may have a suppressive effect on peppers ( Win et al, 2006 ). The highest vitamin C content obtained under the 1.5 μl L –1 treatment during 12 days of storage was in agreement with the previous study by Jiang et al (2018) , who reported that a high concentration of 1-MCP maintained the vitamin C content of yardlong beans after 21 days of storage. According to Lee and Kader (2000) , vitamin C is an antioxidant that reacts with and neutralizes singlet oxygen and other free radicals.…”
Section: Discussionsupporting
confidence: 92%
“…Although the reduction in pepper fruit treated with 1.0 μl L –1 was minimized under the 1-MCP concentrations compared to the control on days 3 and 6, the differences between all treatments on days 9 and 12 were not significant. 1-MCP has been reported to delay chlorophyll degradation in broccoli florets ( Fernández-León et al, 2013 ), Solanum melongena , L ( Massolo et al, 2011 ), Yardlong bean ( Jiang et al, 2018 ), and strawberries ( Li et al, 2016 ). This could be the reason for the observed delay in chlorophyll content in pepper fruit treated with 1.0 μl L –1 during the storage period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The guaiacol method was used to determine the peroxidase (POD) activity . 3.0 mL of 25 mmol L –1 guaiacol and 0.5 mL enzyme extract were added in a test tube, and 200 μL of 0.5 mol L –1 H 2 O 2 solution was added finally, and then immediately measured the absorbance value at 470 nm.…”
Section: Methodsmentioning
confidence: 99%